Prinsip Non-Interference Asean dan Problem Efektivitas Asean Agreement on Transboundary Haze Pollution - Ahmadi, Sidiq (Universitas Muhammadiyah Yogyakarta, 2013)
This paper examines the ineffectiveness ASEAN Agreement on Transboundary Haze Pollution (AATHP). A question that’s been trying to be explained on this paper is Why ASEAN Agreement on Transboundary Haze Pollution can’t run effectively. All this time, the explanation being used that ineffectiveness of AATHP implementation caused by Indonesia who not ratified yet its agreement. It considered as logic because Indonesia is the primary cause of smog that will be tackled by AATHP. The writer’s main argument is ineffectiveness of AATHP influenced by non-interference principle on ASEAN, which really strong and reflected in the content of the agreement which made AATHP legalization is low (soft law). Therefore, with the weak legally binding, even Indonesia ratified the agreement, still the prospect implementation of the effectiveness is low.